2021
DOI: 10.5858/arpa.2020-0451-oa
|View full text |Cite
|
Sign up to set email alerts
|

Interobserver Variation of PD-L1 SP142 Immunohistochemistry Interpretation in Breast Carcinoma: A Study of 79 Cases Using Whole Slide Imaging

Abstract: Context.— The Ventana programmed death ligand-1 (PD-L1) SP142 immunohistochemical assay (IHC) is approved by the US Food and Drug Administration as the companion diagnostic assay to identify patients with locally advanced or metastatic triple-negative breast cancer for immunotherapy with atezolizumab, a monoclonal antibody targeting PD-L1. Objective.— To determine interobserver variability in PD-L1 SP142 IHC interpretation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 17 publications
1
18
0
Order By: Relevance
“…Others have evaluated digitally reporting prognostic immunohistochemical factors such as PDL-1 and HER2 in breast cancers and showed similar concordance results. Two studies of digital HER2 and PDL-1 reporting showed substantially equivalent kappa co-efficient (0.72) and percent agreement ranging from 61% −92 in 180 and 79 cases; respectively 36 , 41 , others have confirmed these findings and concluded there is non-inferiority for interpreting breast markers IHC by either glass slides or digital images 37 .Not surprisingly, 90–97% concordance of glass/digital pairs for all pathologists seen in this study are comparable those published in the literature.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Others have evaluated digitally reporting prognostic immunohistochemical factors such as PDL-1 and HER2 in breast cancers and showed similar concordance results. Two studies of digital HER2 and PDL-1 reporting showed substantially equivalent kappa co-efficient (0.72) and percent agreement ranging from 61% −92 in 180 and 79 cases; respectively 36 , 41 , others have confirmed these findings and concluded there is non-inferiority for interpreting breast markers IHC by either glass slides or digital images 37 .Not surprisingly, 90–97% concordance of glass/digital pairs for all pathologists seen in this study are comparable those published in the literature.…”
Section: Discussionmentioning
confidence: 94%
“…Studies have attempted to use WSI to validate primary diagnosis in multiple surgical pathology specialty applications 12 including prostate 33 , pediatric 6 , dermatopathology 14 , gastrointestinal 16 , 19 , and gynecological pathology specimens 34 . Krenacs et al was among the first to address the potential use of digital imaging in breast cancer 18 .This was further followed by using WSI in primary breast cancer diagnosis 17 , 28 and in reporting prognostic factors such as the Nottingham histology grading 17 , 35 , PDL-1 36 and HER2 immunohistochemistry stains 37 , 38 in histology specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Other immune checkpoint inhibitors such as durvalumab are currently being evaluated in a clinical trial setting. Despite the poor reproducibility of PD-L1 assessment in a prospective multi-institutional assessment [ 47 ], the interobserver variation seems more limited within a single institution [ 48 ]. PD-L1 expression in sTILs might be useful to identify patients at high risk for poor therapeutic response.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the PD-L1/SP142 status of breast cancers depends on the number of tumor-infiltrating immune cells, a combined TILs-PD-L1 assessment may be a logical path forward to pursue [ 19 ]. Previous studies of variable size have reported the interobserver reproducibility of PD-L1/SP142 assessment in breast cancer samples, and their results varied from poor to very good [ 22 , 23 ]. Interobserver variability seems more limited within a single institution [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies of variable size have reported the interobserver reproducibility of PD-L1/SP142 assessment in breast cancer samples, and their results varied from poor to very good [ 22 , 23 ]. Interobserver variability seems more limited within a single institution [ 23 ]. These discrepant results could be explained by the heterogeneous set-up of these studies, with respect to the training and the number of the participating pathologists, and the number of TNBC samples evaluated.…”
Section: Introductionmentioning
confidence: 99%